AB0437 Clinical Utility of Measuring Drug and Anti-Drug Antibody Concentration of Biologic Agents in Rheumatoid Arthritis Patients with Moderate and High Disease Activity. (10th June 2014) - Diana, M.; Iliuta, M.; Gainaru, C.; Apetrei, N.; Luca, G.; Groseanu, L.; Saulescu, I.; Constantinescu, C.; Bojinca, V.; Borangiu, A.; Balanescu, A.; Predeteanu, D.; et al.
Abstract : Background: Biologicals possess a large variation in pharmacokinetics (1). Subtherapeutic drug levels and formation of anti-drug antibodies (ADAb) decrease their efficacy in rheumatoid arthritis (RA) patients (2). Measuring these can become a part of RA management in clinical practice. Objectives: To evaluate the concordance between drug and ADA level and RA clinical activity and to investigate if these correlate to EULAR response at further reevaluation. Methods: All moderate or high disease activity RA patients treated in our clinic between May – December 2013 with rituximab (RTX), infliximab (INF), adalimumab (ADA) and etanercept (ETA) were included in this prospective study. Serum samples for assay of drug level and ADAb titer were collected just before the next administration of the biologic. At next reevaluation (6 months for RTX, 2 months for INF and 4 months for ETA and ADA), patient's clinical response was assessed using EULAR response and was correlated to drug and ADAb level at baseline. Results: 72 RA patients with moderate and high RA disease activity were included. The distribution between biologics was RTX 34.72%, INF 27.77%, ETA 26.38%, and ADA 11.11%. Anti-drug antibodies were found only in 9 INF treated patients - representing 45% of total INF treated patients. Seven of them had undetectable INF level and 2 patients had sub-therapeutic drug level. As expected, presence of anti-INF antibodies correlated negatively with INF serum levels (r=-0.474, P=0.035, ) and also with EULAR response (r=0.681, P=0.001). Sub-therapeutic or undetectable serum drug level were found in 45% patients treated with RTX, 35% in INF group, 15.7% in ETA group and 11, 1% in ADA group. Serum drug level correlated with EULAR response in RTX treated patients at 6 months (r=0.424, P=0.034), in INF treated patients (r=0.701, P=0.001) and in ETA group (r=0.550, P=0.018) at 2 months. Drug level was not correlated to EULAR response (r=0.459, P=0.214) in ADA treated patients, probably due to small sample group (9 patients). Conclusions: Monitoring biological serum drug level might help to optimize therapeutic decisions in patients with moderate or high disease activity. Our study confirmed INF high immunogenicity and it's correlation to serum drug level and consequently to clinical response. Serum drug level just before the next administration correlates with further EULAR response., leading to a better clinical outcome in patients with RA. References: Rieckaert, Charlotte et al. Personalised treatment using serum drug levels of adalimumab in patients wih rheumatoid arthritis:an evaluation of costs and effects. Ann Rheum Dis online Nov 21, 2013; S Garces, M Antunes et al. A preliminary algorithm introducing immunogenicity assessment in the management of patinets with RA receiving tumor necrosis factor inhibitor therapies. Ann Rheum Dis May 11, 2013; Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4821